Nisheeth evan any kavitaen - Joshi, Umashankar (New Delhi Bharatiya Jnanpith, 2005)
collection of Gujrati Potery.
Keywords: Literature- Hindi; Collection of Gujrati Potery; Choudhary, Raghuvir and Patel, Bholabhai tr.; Jnanpith awarded